2020
DOI: 10.21203/rs.3.rs-49671/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing SARS-CoV-2 mutations in the United States

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been mutating since it was first sequenced in early January 2020. The genetic variants have developed into a few distinct clusters with different properties. Since the United States (US) has the highest number of viral infected patients globally, it is essential to understand the US SARS-CoV-2. Using genotyping, sequence-alignment, time-evolution, k-means clustering, protein-folding stability, algebraic topology, and network theory, we reve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 45 publications
(82 reference statements)
1
56
0
1
Order By: Relevance
“…Mutations could be dynamic, as it has been proposed that some mutations like L84S are disappearing, and there is emergence of new ones that render the virus more infective, like S24L that was first sequenced in the USA ( Wang et al, 2020b ). This could explain the weak signal of population expansion whose distribution of S24L, on a large number of sequences, and, at the same time, of L84S increased the Pi value and added some equilibrium with the low frequency of new mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations could be dynamic, as it has been proposed that some mutations like L84S are disappearing, and there is emergence of new ones that render the virus more infective, like S24L that was first sequenced in the USA ( Wang et al, 2020b ). This could explain the weak signal of population expansion whose distribution of S24L, on a large number of sequences, and, at the same time, of L84S increased the Pi value and added some equilibrium with the low frequency of new mutations.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 ORF8 protein has been shown to be implicated in immune evasion by downregulating surface expression of MHC-1 ( Zhang et al, 2020 ). Wang and colleagues ( Wang et al, 2020b ) showed that L84S decreases the function of ORF8, and thus is beneficial for human immune system, whilst S24L increases its function since it reinforces protein folding stability. As for deletions, 382 nts deletion was shown to cause milder infection ( Young et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spike_D614G is one of the most widely discussed mutations. Its presence defines G clade [25], it increases infectivity [32][33][34], mortality [35,36], alters viral fitness [37], and, according to protein modeling, strengthens the folding stability of the spike protein [28]. It is present in 99.2 % of SARS-CoV-2 genomes obtained from Russia (as of 11.11.2020).…”
Section: Discussionmentioning
confidence: 99%
“…Positive binding affinity also indicates that the mutation will help in making tighter interaction with the receptor. 15 Cryo EM studies show that this type of nonsynonymous single nucleotide variations may affect the strength of transmission of the virus. 22 The dynamic studies on a structural basis due to this mutation revealed that the binding surface of the RBD to ACE2 is having largely random coil conformation and it is lacking structural rigidity.…”
Section: Role Of Mutation In Increasing the Stabilitymentioning
confidence: 99%
“…The mutation occurrence from the month of March, 2020 till date is reported as 366 (FIG. 3)and thus this mutant is found to be more prevalent in the United States 15.…”
mentioning
confidence: 99%